Case report: Isolated eyelid metastasis of ccRCC 5 years after receiving radical nephrectomy - Yin, Huaqi; Du, Zheng; Zhang, Jiuwen; Ma, Yongkang; Zhao, Shiming; Yang, Tiejun (Frontiers in Oncology, 2024)
Introduction The most common sites of clear cell renal cell carcinoma(ccRCC) metastasis are the lung, bones, liver and brain; eyelid metastasis is a rare occurrence. Case presentation We report a case of ccRCC metastasis to the left eyelid after radical nephrectomy, and remission after sunitinib treatment. Conclusions Although the probability of eyelid metastasis rate is very low, tumor metastasis to the eyelid skin is possible after radical nephrectomy. Therefore, any rash like changes on the skin during the review procedure cannot be ignored by the physician.